Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan Perdesaan Perkotaan - Waskito Erdi, Tio (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The Indonesian tax system uses land and building tax as one of the most important sources of regional income. Land and building tax has various benefits for both the state and the community. The purpose of this study was to determine the effect of tax literacy, tax sanctions, tax awareness, tax socialization, and the quality of tax authorities' services on taxpayer compliance in paying PBB-P2. The study used convenience sampling and obtained 102 respondents. Respondents in the study were taxpayers who had PBB-P2 tax obligations in Butuh District, Purworejo Regency. The results obtained explained that tax literacy and tax sanctions had an effect on taxpayer compliance, while tax awareness, tax socialization, and the quality of tax authorities' services had no effect on tax compliance.